Meaningful Accountability and Educational Reform - Cynthia J. Reed; Van Dempsey (Educational Considerations, 2003)
States have long been responsible for establishing educational standards and procedures. However, in the past decade the federal government has become increasingly involved in defining how schools are to be held accountable.